Future Cities Laboratory. Indicia 02. - (:unkn) unknown (Lars Müller, 2019)
This second volume in the Future Cities Laboratory Indicia series focuses on the tools, methods, and approaches needed for urban research. In short, following Marshall McLuhan’s famous provocation, the editors focus less on the message and more on the medium of research. This involves retreating from research contents—the topics, themes, questions, hypotheses, insights, ideas, concepts, and thoughts—for the moment to consider the materials, methods, tools, techniques, and approaches that support them. This change in perspective reveals a rich array of research approaches that include: the visual documentation of complex stakeholder interests, political and economic circumstances in built form and design vision; two- and three-dimensional mapping of vegetation, temperature and humidity, in conjunction with point cloud terrestrial and airborne laser-scanning technology; gathering information from sensors and geospatial data; emergence of “solution spaces”and multi-dimensional complexity science; subject oriented approaches to behavioural and cognitive decision making in city navigation; and approaches to emergent phenomena such as extended urbanisation that are not always visible to existing analytical or documentary lenses. The Future Cities Laboratory was established by ETH-Zürich and Singapore’s National Research Foundation (NRF) and operates under the auspices of the Singapore-ETH Centre (SEC).
Keywords: Stadtforschung; Zukunftsperspektive; Verdichtungsraum; Verdichtetes Bauen; Energiesystem; Integrierte Stadtentwicklung; Smart City; Digitalisierung; Urban Governance; Stadtklima; Urbanisierung; Städtewachstum; Stadtrand; Verstädterung; Stadtumland; Big Data